2017
DOI: 10.1016/j.nanoen.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Phonon scattering by nanoscale twin boundaries

Abstract: Twins, as one kind of crystal defects, are often been observed in various material systems. However, its effect on phonon scattering is much less investigated comparing to other defects. The difficulty in understanding the phonon scattering effect by twins lies in the inevitable presence of other defects (e.g., grain boundaries), which overshadow the intrinsic scattering effect by twins. In order to resolve the issue, three different kinds of InSb specimens with microscale grains, nanoscale grains, and nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 57 publications
0
55
0
Order By: Relevance
“…Similar strategy has been applied to other high-performance TE materials such as CoSb 3 [19], Mg 2 Si [20], and PbTe [21]. In addition, it was observed that the phonon scatting induced by TBs can further decrease the lattice thermal conductivity [22]. Despite the important roles of TBs in material properties, their effects on the mechanical properties remain unknown.…”
mentioning
confidence: 94%
“…Similar strategy has been applied to other high-performance TE materials such as CoSb 3 [19], Mg 2 Si [20], and PbTe [21]. In addition, it was observed that the phonon scatting induced by TBs can further decrease the lattice thermal conductivity [22]. Despite the important roles of TBs in material properties, their effects on the mechanical properties remain unknown.…”
mentioning
confidence: 94%
“…Therefore, two basic approaches have been used to enhance the ZT via decreasing the relatively independent lattice thermal conductivity or increasing the power factor (i.e., S 2 σ). Phonon scattering via defect engineering [point defects (8)(9)(10)(11), dislocations (12)(13)(14)(15), and grain boundaries (16,17)] or nanostructuring (18) has led to a significant reduction in lattice thermal conductivity. On the other hand, power factors have also been enhanced via different approaches such as band engineering (19)(20)(21)(22), inducing resonant levels (23), the carrier filtering effect (24)(25)(26)(27), ionized impurity scattering (28), and modulation doping (29,30).…”
mentioning
confidence: 99%
“…Twin boundaries (TBs), a thermodynamically stable planar defect, could provide another phonon scattering source to effectively suppress κ L [36][37][38] [38]. These findings suggest that TBs play significant roles in phonon scattering and κ L reduction without degrading electronic transport properties.…”
mentioning
confidence: 99%